2014
DOI: 10.3109/15412555.2014.898049
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Prevalence and Cessation Characteristics among U.S. Adults With and Without COPD: Findings from the 2011 Behavioral Risk Factor Surveillance System

Abstract: Adults with COPD were just as likely as those without COPD to make a past-year quit attempt; however, approximately 40% of smokers with COPD did not try to quit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 15 publications
4
19
5
Order By: Relevance
“…Recent studies performed in the USA found smoking rates between 35% and 45% among adult patients with COPD 28,29. In our series, the prevalence of active smokers is 55%, contrasting with reports recently published in Spain that set it at about 25% 22,23.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent studies performed in the USA found smoking rates between 35% and 45% among adult patients with COPD 28,29. In our series, the prevalence of active smokers is 55%, contrasting with reports recently published in Spain that set it at about 25% 22,23.…”
Section: Discussioncontrasting
confidence: 99%
“…Given a shared risk factor (which accounts for up to 25% of all strokes and is found in twice as many COPD vs non-COPD patients) (6, 7) smoking, it stands to reason that both stroke and COPD would co-exist in certain individuals. However, the rate of COPD among stroke patients has not previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“…1 Among patients with diagnosed COPD in the United States, the prevalence of current smoking was higher than that among adults without COPD or other chronic diseases (47.3 vs. 20.0%, respectively). 2 Interestingly, despite this difference in smoking prevalence, motivation to quit smoking does not differ between smokers with COPD and without COPD, 3 and current smokers with COPD were just as likely as smokers without chronic diseases to make a pastyear quit attempt (59.7 vs. 53.9%, respectively) and even more likely to avail themselves of smoking cessation resources, such as a telephone quitline or pharmacotherapy (p < 0.001). 2 Those who eventually succeed in quitting and remaining abstinent often do so only after multiple attempts.…”
Section: Smoking Cessationmentioning
confidence: 91%